Gemydd, Y - Lewis, Caryl (Y Lolfa, 2007)
A novel which examines solitary lives, and provides powerful portrayals of characters who work in a market that's about to close. The narrative focuses on Mair who makes a living out of jewellery and house clearances - that is, until she finds one jewel that transforms her life completely. Intro – Pennod 1 – Pennod 2 – Pennod 3 – Pennod 4 – Pennod 5 – Pennod 6 – Pennod 7 – Pennod 8 – Pennod 9 – Pennod 10 – Pennod 11 – Pennod 12 – Pennod 13 – Pennod 14 – Pennod 15 – Pennod 16 – Pennod 17 – Pennod 18 – Pennod 19 – Pennod 20 – Pennod 21 – Pennod 22 – Pennod 23 – Pennod 24 – Pennod 25 – Pennod 26 – Pennod 27 – Pennod 28 – Pennod 29 – Pennod 30 – Pennod 31 – Pennod 32 – Pennod 33 – Pennod 34 – Pennod 35 – Pennod 36 – Pennod 37 – Pennod 38 – Pennod 39 – Pennod 40.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books